A study of the influence of plasma–molecule interactions on particle balance during detachment. (March 2021) - Verhaegh, Kevin; Lipschultz, Bruce; Harrison, James; Duval, Basil; Bowman, Chris; Fil, Alexandre; Gahle, Daljeet Singh; Moulton, David; Myatra, Omkar; Perek, Artur; Theiler, Christian; Wensing, Mirko; et al.
Abstract: In this work we provide experimental insights into the impact of plasma–molecule interactions on the target ion flux decrease during divertor detachment achieved through a core density ramp in the TCV tokamak. Our improved analysis of the hydrogen Balmer series shows that plasma–molecule processes are strongly contributing to the Balmer series intensities and substantially alter the divertor detachment particle balance. We find that Molecular Activated Recombination (MAR) ion sinks from H 2 + (and possibly H − ) are a factor ∼ 5 larger than Electron–Ion Recombination (EIR) and are a significant contributor to the observed reduction in the outer divertor ion target flux. Molecular Activated Ionisation (MAI) appears to be substantial during the detachment onset, but further research is required into its magnitude given its uncertainty. Plasma–molecule interactions enhance the Balmer line series emission strongly near the target as detachment proceeds. This indicates enhancements of the Lyman series, potentially affecting power balance in the divertor. As those enhancements vary spatially in the divertor and are different for different transitions, they are expected to result in a separation of the L y β and L y α emission regions. This may have implications for the treatment and diagnosis of divertor opacity. The demonstrated enhancement of the Balmer series through plasma–molecule processes potentially poses a challenge to using the Balmer series for understanding and diagnosing detachment based only on atom–plasma processes. Highlights: Plasma–molecule interactions (PMI) result in excited hydrogen atoms PMI strongly enhances atomic line emission and shifts H α towards target PMI enhancement of Balmer series poses a challenge to diagnostic interpretation PMI impacts particle balance through Molecular Activated Recombination (MAR) Measured MAR ≈ 5 x Electron-Ion Recombination, occurs at T e = [ 1 . 5 − 3 ] eV